Unravelling the Taiwan question : a discussion on the historical background, theoretical issues, policy approaches, the present and the future : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy (Defence and Strategic Studies) at Massey University, Palmerston North, New Zealand - Huang, Dai-zhi (Massey University, 2008)
The Taiwan question is a multi fold story with complexity and outsiders of China may not grasp a full picture of the question. Taiwan is a part of China and the idea is taken for granted for Chinese, but not debate-free in the world. This thesis aims to resolve some misunderstandings in the debate. The thesis is composed of four chapters. The first chapter will discuss Chinese people’s altitude on national unity and delineates the historical background of the Taiwan question with a focus on its bond with the Chinese Mainland. Some theoretical issues, relevant to the Taiwan question, such as sovereignty, self-determination right and so on, will be discussed in the second chapter. Chapter three will brief policy approaches across the Taiwan Strait. The updated situation and the Taiwan question’s possible future will be presented in the fourth chapter.
Keywords: China and Taiwan; Sovereignty; National unity; Fields of Research::360000 Policy and Political Science::360200 Policy and Administration::360204 Defence studies